Konsep Arsitektur Berkelanjutan pada Kawasan Agrowisata Durian di Desa Bulo, Polewali Mandar - Zalzabila, Alyfiah Annisa; Tauhid, Fahmyddin A'raaf; Hildayanti, Andi (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Abstract_ The Covid-19 pandemic has had a significant impact on the tourism sector, even though this sector is one of the main contributors to Indonesia's economy. Bulo Village, located in Bulo District, Polewali Mandar Regency, has great potential for the development of an agro-tourism area. Geographically, this village is located in a mountainous area with an area of durian plantations covering approximately 200 hectares, which is the main attraction. However, to develop this potential into an attractive tourist destination, many aspects still need improvement, both in terms of infrastructure and the management of natural and human resources. Therefore, this research aims to design an agrotourism area in Bulo Village with a sustainable architecture approach that considers the balance between environmental, economic, and social aspects. The method used in this research is a sustainable architectural design approach, which focuses on the efficient use of natural resources without damaging the local ecosystem. The results of this design are expected to contribute to the development of an environmentally friendly agro-tourism area, support the local economy, and improve the social welfare of the village community. Keywords: Agrotoursm; Sustainable Architecture; Polewali Mandar.